Nestmate Recognition and Cuticular Hydrocarbons of Two Sympatric Species of Reticulitermes in Japan (Isoptera: Rhinotermitidae) - Takematsu, Yoko (Sociobiology, 2014)
The nestmate recognition of two sympatric species, R. kanmonensis and R. speratus, was investigated in terms of agonistic behavior and trophallactic behavior. R. speratus showed strong agonistic behavior against different species, but no trophallactic contact with them. However, agonistic behavior against different colonies of the same species was weak, and trophallactic exchange of food was observed. On the other hand, R. kanmonensis showed strong agonistic behavior not only against different species but also against different colonies of the same species, and trophallactic contact was absent. These results indicate that R. kanmonensis does not exhibit colony fusion, unlike R. speratus, which is known to exhibit colony fusion. This marked difference in the occurrence of colony fusion can be related to the difference in the distribution pattern of the two species. Cuticular hydrocarbons of both species were also analyzed. Relatively high hydrocarbon homogeneity was observed among colonies in R. kanmonensis compared to R. speratus.